Energy Efficient Design of Wireless Sensor Network: Clustering - Murthy Garimella, Ram; Reddy Edla, Damodar; Kuppili, Venkatanareshbabu (International Journal of Engineering and Technology, 2018)
One of the significant criteria of wireless sensor network is energy efficiency. Focused on the energy problem, researchers design a few algorithms based on clustering in the present era but lack of proper mathematically rigor justification. To fill this research gap, a system and method has been proposed with a mathematical proof induced from the concept of Hessian matrix of multi variable calculus for Energy efficient techniques of data gathering or routing in Wireless Sensor Networks. It is assumed that Wireless Sensor Nodes are distributed in a multidimensional space.  Illustrations verify that the proposed system mathematical design for any clustering approach promises a low-energy communication structure.